Descriptive analysis of the english teacher’s code switching - Nurul Isma Ishak; Muhammad Zuhri Dj.; Hasriati Nur (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This study aims to determine the code-switching used by English teachers in teaching English at SMA Pesantren Putri Al-Manawwarah. There is one problem in this study, namely the types of code-switching used by the research subject in teaching and learning of English at SMA Pesantren Putri Al-Manawwarah. The researchers conduct descriptive-qualitative research. This study uses a qualitative approach because the data are spoken. Therefore, it is interesting to observe this phenomenon to find out the types. The data collection are; observation, recording, and note. The result of this study shows that the details of code-switching used by the teacher. In the English teaching and learning process within 2x45 minutes, there are 114 utterances in English teaching and learning process which are pronounced by the teacher. There are three types of code-switching (inter sentential code-switching, Intra sentential code-switching, and tag switching). According to the type, there are 59 utterances of code-switching. The number of inter sentential code-switching is 31 utterances (53%), Intra sentential code-switching is 14 utterances (24%), and tag switching is 14 utterances (24%).